Increasing women’s participation in wildlife governance in Zambia - Sommerville, Matt; Bessa, Thais; Malasha, Patricia; Dooley, Meagan (Frontiers in Conservation Science, 2022)
Community-based natural resource management bodies, including Community Resource Boards (CRBs) and Community Scouts, are responsible for governance and wildlife law enforcement in Zambia’s Game Management Areas (GMA), community lands that buffer the National Parks. Despite commitments to inclusive governance and benefit sharing, men dominate the wildlife and natural resource sectors in Zambia; making up the vast majority of wildlife scouts who patrol the GMAs and hold most positions on the CRBs who allocate benefits and decide on management priorities. Gender blind structures within community governance institutions during the recruitment and training process and social and gender norms that see leadership roles as men’s domain act as barriers to women’s participation in the sector. In response, the United States Agency for International Development (USAID) invested in a comprehensive package of activities to increase women’s effective participation in wildlife governance and law enforcement, including gender-responsive CRB elections, empowerment training for newly elected women candidates, revised community scout training curriculum, and capacity building support for organizations that support scouts and CRBs. The intervention helped increase women’s representation in CRBs from four percent to 25 percent in pilot communities. It also supported the Department of National Parks and Wildlife to recruit the first gender balanced cohort of community scout recruits and fielded an all-women patrol unit in Lower Zambezi National Park.